Biodiesel Production through Electrolysis Using an Ionic Liquid, 1-Ethyl-3-Methylimidazolium Chloride as a Supporting Electrolyte. (31st March 2023) - Aregawi, Beyene Hagos; Nguyen, Hoang Chinh; Fu, Chun-Chong; Ong, Hwai Chyuan; Barrow, Colin J.; Su, Chia-Hung; Wu, Shao-Jung; Juan, Horng-Yi; Wang, Fu-Ming
Abstract : Electrolysis is a promising approach for biodiesel production. However, low electrical conductivity of a reaction mixture results in a low reaction rate. Thus, this study developed a novel catalyst-free electrolysis process using an ionic liquid as a supporting electrolyte for biodiesel production. Various ionic liquids were assessed, and 1-ethyl-3-methylimidazolium chloride ([Emim]Cl) exhibited the highest electrical conductivity (4.59 mS/cm) and the best electrolytic performance for transesterification. Electrolysis in the presence of [Emim]Cl was subsequently optimized using response surface methodology to maximize biodiesel yield. A maximum biodiesel yield of 97.76% was obtained under the following optimal reaction conditions: electrolysis voltage, 19.42 V; [Emim]Cl amount, 4.43% (w / w ); water content, 1.62% (w / w ); methanol to oil molar ratio, 26.38 : 1; and reaction time, 1 h. Notably, [Emim]Cl could be efficiently reused for at least three cycles with a corresponding biodiesel yield of 94.81%. Moreover, the properties of the synthesized biodiesel complied with EN and ASTM standards. The findings of this study indicate that catalyst-free electrolysis using [Emim]Cl as a supporting electrolyte is an eco-friendly and efficient method for biodiesel production.